Lipid Profiles of Adipose and Muscle Tissues in Mouse Models of Juvenile Onset of Obesity without High Fat Diet Induction: A Fourier Transform Infrared (FT-IR) Spectroscopic Study. Issue 6 (June 2015) - Sen, Ilke; Bozkurt, Ozlem; Aras, Ebru; Heise, Sebastian; Brockmann, Gudrun Anni; Severcan, Feride
The current study aims to determine lipid profiles in terms of the content and structure of skeletal muscle and adipose tissues to better understand the characteristics of juvenile-onset spontaneous obesity without high fat diet induction. For the purposes of this study, muscle (longissimus, quadriceps) and adipose (inguinal, gonadal) tissues of 10-week-old male DBA/2J and Berlin fat mouse inbred (BFMI) lines (BFMI856, BFMI860, BFMI861) fed with a standard breeding diet were used. Biomolecular structure and composition was determined using attenuated total reflection Fourier transform (ATR FT-IR) spectroscopy, and muscle triglyceride content was further quantifed using high-performance liquid chromatography (HPLC) coupled with an evaporative light scattering detector (ELSD). The results revealed a loss of unsaturation in BFMI860 and BFMI861 lines in both muscles and inguinal adipose tissue, together with a decrease in the hydrocarbon chain length of lipids, especially in the BFMI860 line in muscles, suggesting an increased lipid peroxidation. There was an increase in saturated lipid and triglyceride content in all tissues of BFMI lines, more profoundly in longissimus muscle, where the increased triglyceride content was quantitatively confrmed by HPLC-ELSD. Moreover, an increase in the metabolic turnover of carbohydrates in muscles of the BFMI860 line was observed. The results demonstrated that subcutaneous (inguinal) fat also displayed considerable obesity-induced alterations. Taken together, the results revealed differences in lipid structure and content of BFMI lines, which may originate from different insulin sensitivity levels of the lines, making them promising animal models for spontaneous obesity. The results will contribute to the understanding of the generation of insulin resistance in obesity without high fat diet induction.